Book Review: Krishna Kumar, Smaller Citizens: Writings on the Making of Indian Citizens. Issue 2 (December 2021) - Swaminathan, Padmini
Krishna Kumar, Smaller Citizens: Writings on the Making of Indian Citizens . Orient BlackSwan, 2021, xviii + 150 pp., ₹395. ISBN: 9789354 420801(Paperback).